2016
DOI: 10.3727/096368915x687921
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cells Accelerate Diabetic Wound Healing through the Induction of Autocrine and Paracrine Effects

Abstract: Cell-based therapy is an attractive approach for the treatment of chronic nonhealing wounds. This study investigated whether adipose-derived stem cells (ASCs) can accelerate diabetic wound healing and traffic in the engraftment of ASCs. Dorsal full-thickness skin wound defects (6 × 5 cm) were created in a streptozotocin (STZ)-induced diabetes rodent model. Group I served as a nondiabetic normal control, group II served as a diabetic control without ASCs, and group III included rats that were injected subcutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
105
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 39 publications
4
105
1
Order By: Relevance
“…We hypothesize that the additional benefits observed with betatrophin overexpression may result from the combination of betatrophin and growth factors secreted by MSCs and/or from the immunomodulatory and anti-apoptotic properties of the ADMSCs. The anti-inflammatory capacity of the ADMSCs observed in the present study was consistent with a previous study by Kuo et al (63), which showed that ADMSCs accelerated diabetic wound healing by reducing the pro-inflammatory environment and increasing growth factor expression.…”
Section: Discussionsupporting
confidence: 93%
“…We hypothesize that the additional benefits observed with betatrophin overexpression may result from the combination of betatrophin and growth factors secreted by MSCs and/or from the immunomodulatory and anti-apoptotic properties of the ADMSCs. The anti-inflammatory capacity of the ADMSCs observed in the present study was consistent with a previous study by Kuo et al (63), which showed that ADMSCs accelerated diabetic wound healing by reducing the pro-inflammatory environment and increasing growth factor expression.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast with the expected and found in other studies 8,11 , there was no difference in microscopic evaluation, the inflammatory process was not changed. Probably in immunohistochemistry evaluation the results would be more satisfying.…”
Section: Resultscontrasting
confidence: 55%
“…There is a dependent of fibroblast growth factor, autocrine and paracrine secretion of substances as tipe I collagen and neoangiogenesis 8,16 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The superficial localization of infection in the wound enables exciting new perspectives by means of in vivo imaging systems in chronic wound science. 63 …”
mentioning
confidence: 99%